[UF6]2−: A Molecular Hexafluorido Actinide(IV) Complex with Compensating Spin and Orbital Magnetic Moments. Issue 44 (7th August 2019) - Pedersen, Kasper S.; Meihaus, Katie R.; Rogalev, Andrei; Wilhelm, Fabrice; Aravena, Daniel; Amoza, Martín; Ruiz, Eliseo; Long, Jeffrey R.; Bendix, Jesper; Clérac, Rodolphe
Abstract: The first structurally characterized hexafluorido complex of a tetravalent actinide ion, the [UF6 ] 2− anion, is reported in the (NEt4 )2 [UF6 ]⋅2 H2 O salt (1 ). The weak magnetic response of 1 results from both U IV spin and orbital contributions, as established by combining X‐ray magnetic circular dichroism (XMCD) spectroscopy and bulk magnetization measurements. The spin and orbital moments are virtually identical in magnitude, but opposite in sign, resulting in an almost perfect cancellation, which is corroborated by ab initio calculations. This work constitutes the first experimental demonstration of a seemingly non‐magnetic molecular actinide complex carrying sizable spin and orbital magnetic moments. Abstract : The electronic ground state of the weakly magnetic U IV was studied in great detail for the simple structurally characterized [UF6 ] 2− anion, combining X‐ray absorption spectroscopy, magnetometry, and quantum‐chemical calculations. The decomposition and quantification of the relatively large spin and orbital magnetic moments provide key information for an improved understanding of the complex electronic structures of actinide ions.